Implementation of artificial intelligence in biotechnology for rapid drug discovery and enabling personalized treatment through vaccines and therapeutic products - Anirudh Mehta (BULLET : Jurnal Multidisiplin Ilmu, 2022)
A new era of healthcare and biomedical research has been brought about by the merging of biotechnology with artificial intelligence (AI). This integration presents previously unheard-of prospects to expand scientific understanding, expedite medication discovery, and tailor therapies. In this study, we examine the ways in which biotechnology and artificial intelligence might work together to improve healthcare in a number of areas, such as individualized treatment plans, quick drug discovery, and the creation of therapeutic items. We go over how artificial intelligence (AI) algorithms use massive amounts of biological and chemical data to forecast medication success, optimize treatment plans, and speed up the search for new treatments. We also look at how biotechnology can be used to translate AI-driven predictions into interventions that are applicable to clinical settings, such as the creation of customized vaccinations, gene therapies, and products for regenerative medicine. We draw attention to the difficulties and constraints that come with integrating biotechnology and AI in healthcare, such as the complexity and interpretability of the data, ethical issues, legal barriers, and societal ramifications. Lastly, we talk about the potential applications of biotechnology and AI in healthcare going forward, such as the creation of more understandable AI algorithms, the fusion of systems biology and multi-omics data, and the development of customized medical devices and regenerative medicine treatments. We can fully utilize biotechnology and AI to change healthcare delivery, enhance patient outcomes, and influence the course of medicine by tackling these issues and embracing these new approaches.